Experimental evaluation of the performance and power output enhancement of a divergent solar chimney power plant by increasing the chimney height - Reemal Prasad; M. Rafiuddin Ahmed (Frontiers in Energy Research, 2024)
Solar energy is an attractive renewable energy option for countries located in the tropical region. Harvesting this energy using simple yet innovative technologies such as solar chimney power plants (SCPP) will help the developing countries in meeting their sustainable development goals. In an SCPP, air is heated under a greenhouse collector and the hot air is passed to a chimney, where it drives a turbine while rising up. Research efforts have been directed in the past at improving the performance and power output of an SCPP by varying its geometric parameters. The chimney height of a previously optimized solar chimney power plant, having a divergent chimney, was increased from 4 to 6 m and then to 8 m in this first experimental work of this kind. The temperature variations inside the collector, along the chimney height, the velocity at the turbine section, the power available and the output power of an air turbine, estimated by applying mechanical load, are compared for the three chimney heights. The temperature rise of the air inside the collector was the highest for the 4 m tall SCPP and reduced as the chimney height was increased to 6 and 8 m due to the lower time of stay of air in the collector for greater chimney heights. Along the height of the divergent chimney, the temperature dropped with the maximum drop occurring for the 8 m tall SCPP indicating a lower enthalpy loss at the chimney exit. The air velocity at the turbine section was found to increase with chimney height for given solar insolation/time of the day due to the higher driving force which is the buoyancy effect produced by the hot air. The maximum turbine output power for the 8 m tall SCPP increased by 252% compared to the 4 m tall SCPP indicating that significant improvement in the power output can be achieved by increasing the height of a divergent chimney SCPP. An average power of about 40 kW will be available for a chimney height of 100 m which will be extremely beneficial for the sustainable development of small islands.